Charisma and Everyday Life in the Economic Field - Valeria Kalinina (Journal of Economic Sociology, 2024)
Much of the discussion surrounding Max Weber's category of charisma focuses on the processes of routinization and objectification, which result in depersonalization and the loss of revolutionary character in the originally personal quality. However, there are examples where personal and routinized types overlap. In such cases, the proclaimed ideas are extraordinary and innovative, but are limited to an isolated sphere of influence and do not claim the status of comprehensive revolutionary principles. On the other hand, the personal character is preserved, avoiding the depersonalization typical of routinized forms. A number of questions arise: Is there a place for charisma in such cases? Is it appropriate to speak of an everyday version of the phenomenon while avoiding a “benevolent” character? In order to distinguish those cases when, in contrast to the fabricated character, the use of the category is permissible and appropriate, it is necessary to turn to the genesis of everyday charisma. For this purpose, the central argument of the article is grounded in the modified classical content of the term proposed by K. Kremer in the context of market constellations analysis. As a consequence, based on the proposed approach in combination with the works of N. Biggart, W. Bachmann, R. Sennett, S. N. Eisenstadt, P. Bourdieu, S. Turner, A. Bienfais and E. Horn, the paper systematizes the idea of the process in constructing everyday charisma, the mechanism of imitation and subordination and the ways of strengthening the legitimacy of everyday charisma. The examples of K. Kremer's “economic actor” and retail strategies of luxury brands demonstrate the possibilities of applying the category of charisma to the cases when the blending of economic and social foundations leads to a shift away from rational motivations of economic actors to maximize their utility.